1985
DOI: 10.1007/bf02541834
|View full text |Cite
|
Sign up to set email alerts
|

A calorimetric, NMR and X‐ray diffraction study of the melting behavior of tripalmitin and tristearin and their mixing behavior with triolein

Abstract: X-ray diffraction, differential scanning calorimetry and NMR have been used to give information on the molecular order and melting of tripalmitin and tristearin crystals. They also have been used to study the melting and solubility of these pure triglycerides when mixed with triolein. From these studies we propose demixing in the liquid state and observe modification of the crystallization kinetics of these saturated triglycerides such that the highest melting (/~-polymorphic) form is observed within a minute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
51
2
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 24 publications
8
51
2
2
Order By: Relevance
“…This was higher than the ratio of 1 : 7 reported by Norton et al [6] at 60 MHz and Azoury et al at 20 MHz. [7] These differences can be easily explained by the different tempering procedures, as well as the different magnetic fields and temperatures studied.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…This was higher than the ratio of 1 : 7 reported by Norton et al [6] at 60 MHz and Azoury et al at 20 MHz. [7] These differences can be easily explained by the different tempering procedures, as well as the different magnetic fields and temperatures studied.…”
Section: Discussioncontrasting
confidence: 63%
“…The current results are in agreement with previous studies performed with one or two TAs at a single temperature. [6,7,13,14] The present study demonstrated that a general dynamic behavior can be observed for TAs at low or high NMR field whatever the chain length and the temperature studied. The results obtained from the proton T 1 measurements displayed a minimum ratio of 1 : 10 between the α and the β forms for the TA family chosen.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Thus, the introduction of unsaturated acyl chains in a saturated fat system by the blending of saturated and unsaturated TAG (StStSt and OOO, respectively) does not significantly change the principal sequence of structural transformations, apart from the formation of mixed crystals of the phases already known for the components of the blend. Fast cooling introduces more randomness in the structure detected by DSC [25]. These experiments suggest that the formation of the a 2 -phase in the mixed saturated/unsaturated TAG is solely the result of a molecular composition including both saturated and unsaturated hydrocarbon chains in one molecule and not the result of a mixed composition of saturated and unsaturated hydrocarbon chains.…”
Section: Ststst-ooo Blendsmentioning
confidence: 73%
“…In contrast, the T 1 of the α form of tristearin (hexagonal form) has been measured at 250 ms, while that of the β form (triclinic form) is 1.7 s [10]. According to Azouri [10], Norton [11] was the fi rst to use the parameter T 1 to diffe re n t i ate poly m o rp h i c forms.…”
Section: Introductionmentioning
confidence: 99%